2016
DOI: 10.1136/flgastro-2015-100681
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring thiopurine metabolites in inflammatory bowel disease

Abstract: Thiopurines (azathioprine and mercaptopurine) are one of the immunosuppressive mainstays for the treatment of inflammatory bowel disease. In spite of its widespread use, thiopurine metabolism is still not fully understood, and a significant proportion of patients suffer toxicity or lack of efficacy. Different enzymatic pathways with individual variations constitute a pharmacogenetic model that seems to be suitable for monitoring and therapeutic intervention. This review is focused on current concepts and recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…One of the strongest ways to determine initial 6-MP dose is an experimental assessment of potential for drug adverse reactions, such as severe neutropenia by monitoring 6-MP metabolite concentration or using in vitro activity profiles (Dubinsky et al, 2000; Ansari et al, 2002;; Cuffari, 2005; Bradford, 2011; Supandi et al, 2018). However, applying such methods into routine clinical practice for predicting drug-induced toxicity is still challenging because it is extremely time-consuming, expensive, and inefficient (González-Lama and Gisbert, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One of the strongest ways to determine initial 6-MP dose is an experimental assessment of potential for drug adverse reactions, such as severe neutropenia by monitoring 6-MP metabolite concentration or using in vitro activity profiles (Dubinsky et al, 2000; Ansari et al, 2002;; Cuffari, 2005; Bradford, 2011; Supandi et al, 2018). However, applying such methods into routine clinical practice for predicting drug-induced toxicity is still challenging because it is extremely time-consuming, expensive, and inefficient (González-Lama and Gisbert, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hematological toxicity in the form of myelosuppression, secondary to either thiopurine or elevated levels of its metabolite 6-thioguanine (6-TGN), is the most serious ADR. A review of 66 trials including 8302 patients reported a cumulative incidence of myelosuppression of 7%, predominantly occurring within the initial few months of treatment [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…In most populations, approximately 10% of individuals are heterozygotes and a further 0.3% carry homozygous variants of the non-functional TPMT alle les. 14,20,21,24,25 In the present study, none of the participating patients were identified as being homozygous for any mutation. TPMT genotyping has been demonstrated to show high sensitivity, 19,23,26 with reported sensitivities and specificities of 88.9% (81.6-97.5%) and 99.2% (98.4-99.9%), respectively.…”
Section: Discussionmentioning
confidence: 75%